Dynamic characterisation of an exhaust system / Abdul Rani Muhamad Norhisham … [et al.] - Muhamad Norhisham, Abdul Rani; Mat Isa, Ahmad Azlan; Abdul Rahman, Zuriah; Ali Al-Assadi, Hayder M. A. (UiTM Press, 2011)
This paper is concerned with the identification of the dynamic characteristics of a continuous structure. It presents the Transfer Matrix Method (TMM) as an alternative approach to determine the structural properties of a single line type structure. Firstly, a TMM is introduced to model and describe the dynamics of a continuous structure. An algorithm based on this method is then developed and applied to a real automotive exhaust system which represents a complex continuous structure in order to obtain the natural frequencies and the corresponding mode shapes. The results are then validated through simulation model using the Finite Element Method via commercially available software. Both methods yield very comparable results and, hence, prove the developed algorithm as a notable alternative solution.